A Bayesian Approach to Combining Conditional Demand and Engineering Models of Electricity Usage - Caves, Douglas W.; Herriges, Joseph A.; Train, Kenneth E.; Windle, Robert J. (The Review of Economics and Statistics, 1987)
Douglas W. Caves, Joseph A. Herriges, Kenneth E. Train, Robert J. Windle, A Bayesian Approach to Combining Conditional Demand and Engineering Models of Electricity Usage, The Review of Economics and Statistics, Vol. 69, No. 3 (Aug., 1987), pp. 438-448